Methods and means of developing academic talent of students in universities of the PRC - H. Tiwen (Професійна освіта: методологія, теорія та технології, 2023)
In the article, a psychological and pedagogical analysis of the theoretical aspect of the development of academic giftedness of students in universities of the People’s Republic of China is carried out. The purpose of the article is to characterize the methods and means of developing students’ academic talent in Chinese universities. An extensive list of research methods is used to study this aspect. Some of these methods include the analysis of historical sources, comparative analysis and synthesis. Results. Academic giftedness of students is a high level of intellectual development (ability to quickly and deeply absorb knowledge, ability to analyze information, draw logical conclusions and solve problems, developed memory, attention and imagination); persistent motivation to study (persistent interest in knowledge and new research, desire for independent learning and development, ability to set goals and achieve them); creative abilities (ability to generate new ideas and find nonstandard solutions, ability to see a problem from different perspectives, developed creativity and originality of thinking); emotional intelligence (ability to understand and manage one’s emotions, ability to establish communication with other people, developed empathy and compassion); leadership qualities (the ability to lead people and organize work; the ability to accept responsibility and take the initiative; developed communication and organizational skills. The structure of academic giftedness of students is a complex and multifaceted system that includes the following components: cognitive (intelligence, cognitive abilities, memory attention, thinking), motivational (cognitive motivation, achievement, interest in learning, dedication), creative (creativity, originality, flexibility of thinking, imagination), emotional (emotional intelligence, self-regulation, empathy, stress resistance), personal (leadership qualities, responsibility, independence, initiative). The Chinese experience shows that it is necessary to continue the development of theoretical foundations, as well as practical approaches to the creation of methods and means of developing the academic giftedness of students in Chinese universities. Conclusions. The education system of academically gifted students in the universities of the PRC includes early identification and support, testing, programs for gifted students, supportive environment, scholarships and grants, mentoring, innovative approaches to learning, cooperation with other countries and development of personal qualities such as creativity, critical thinking and leadership skills. Features of the educational content and teaching methods of gifted students include the introduction of accelerated learning and «expansion» and «enrichment» courses of the program; growing role of effective teaching methods and modern technologies in the development of students’ academic abilities. Universities in China take different approaches to teaching students who have academic ability. These include traditional forms of learning such as lectures, seminars and practicals; innovative forms of education, such as problem-based learning, project-based learning, case methods, distance learning; interactive forms of learning such as discussions, role-plays and research. The use of modern information technologies, such as virtual laboratories, online libraries, and social networks, is an important component of the development of academically gifted students in Chinese universities